Semi-quantitative evaluation of waterlogging duration using two models based on soil colour in a representative upland catchment of northern Lao PDR - Bourdon, Emmanuel; Blavet, D.; Luankongkam, O.; Soulileuth, B.; Chanhphengxay, A.; Pierret, Alain; Ribolzi, Olivier (2008)
Groundwater is a vital resource for rural populations in tropical areas who depend on seasonal rainfall. Groundwater is often the only source of water feeding streams, allowing them to flow throughout the dry season. The aim of this study was to evaluate two models for estimating the average duration that soil is waterlogged by shallow groundwater table. These models, based on variations in soil colour, were developed by Blavet et al (2000) from observations and measurements made in a semi-arid environment in West Africa. Therefore there is a need to evaluate whether these models are also pertinent in a mountainous context of northern Laos. Our approach consisted in comparing data obtained from field measurements (water table level, morpho-pedological features including soil colour) with predictions made by the models. This study was carried out along two transects with contrasting characteristics in terms of the landscape morphology as well as the soil hydrodynamic: the first was in an open swampy valley with convex hillslopes, the second was in a steep-banked and narrow valley with convexo-concave hillslopes. Preliminary results from our study identified relationships between soil colour and the mean rate of soil waterlogging and are a first step for developing an inexpensive and simple method to predict soil saturation in this environment.